Implementation of the Play-Based Learning Method in Dance Arts Learning to Enhance Early Childhood Creativity at As-Solehah Kindergarten, Bawen - Novia Ayu Aulia; Rimasari Pramesti Putri (Universitas Muhammadiyah Enrekang, 2025)
This study aims to describe the implementation of the play-based learning method in dance education as a strategy to enhance early childhood creativity at TK As-Solehah Bawen. Creativity is an essential aspect of child development that can be nurtured through expressive, arts-based activities. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects included a dance teacher, the school principal, and early childhood students. The findings reveal that play-based learning was implemented through activities that integrate play, imagination, and movement exploration, such as role-playing, improvisational dance, and thematic movement. The teacher acted as a facilitator who provided movement stimuli and allowed space for the children to express themselves freely. This method was proven to increase student engagement, self-confidence, and originality in movement. Furthermore, a joyful and contextual learning environment helped strengthen the growth of children's creativity. The analysis of this study draws on Vygotsky’s sociocultural development theory, particularly the concepts of the zone of proximal development, scaffolding, and imaginative play, which emphasize the role of social interaction and play in supporting children's cognitive and creative development. This study recommends strengthening teachers’ capacity to design systematic and sustainable play-based dance education in early childhood learning settings